Comorbidity of severe psychotic disorders with measures of substance use - Hartz, Sarah M. (2014)
IMPORTANCE: Although early mortality in severe psychiatric illness is linked to smoking and alcohol, no studies have comprehensively characterized substance use behavior in severe psychotic illness. In particular, recent assessments of substance use in individuals with mental illness are based on population surveys that do not include individuals with severe psychotic illness. OBJECTIVE: To compare substance use in individuals with severe psychotic illness to substance use in the general population. DESIGN: We assessed comorbidity between substance use and severe psychotic disorders in the Genomic Psychiatry Cohort (GPC). The GPC is a clinically assessed, multi-ethnic sample consisting of 9,142 individuals with the diagnosis of schizophrenia, bipolar disorder with psychotic features, or schizoaffective disorder, and 10,195 population controls. PRIMARY OUTCOME MEASURES: Smoking (smoked > 100 cigarettes lifetime), heavy alcohol use (> 4 drinks/day), heavy marijuana use (>21 times of marijuana use in a single year), and recreational drug use. RESULTS: Relative to the general population, individuals with severe psychotic disorders have increased risk of smoking (OR 4.6, 95% CI 4.3-4.9), heavy alcohol use (OR 4.0, 95% CI 3.6-4.4), heavy marijuana use (OR 3.5, 95% CI 3.2-3.7), and recreational drug use (OR 4.6, 95% CI 4.3-5.0). All ethnicities (African American, Asian, European American, and Hispanics) and both sexes have greatly elevated risks of smoking, alcohol, marijuana, and drug use. Of specific concern, recent public health efforts that have successfully decreased smoking among individuals under age 30 appear to have been ineffective among individuals with severe psychotic illness (p-value for interaction effect between age and severe mental illness on smoking initiation P=4.5 × 10(−5)). CONCLUSIONS AND RELEVANCE: In the largest assessment of substance use among individuals with severe psychotic illness to date, we found odds of smoking, alcohol, and other substance use to be dramatically higher than recent estimates of substance use in mild mental illness.